Measuring the Infectiousness of Persons with HIV-1: Opportunities for Preventing Sexual HIV-1 Transmission - Baeten, J.M.; Overbaugh, J. (Current HIV Research, 2003)
Methods to reduce sexual transmission of HIV-1 are urgently needed to slow the global HIV-1 epidemic. These methods should include interventions that minimize susceptibility in uninfected populations at risk, as well as interventions that decrease the infectiousness of HIV-1 infected individuals. Surprisingly few interventions to prevent HIV-1 transmission have been targeted at persons who are already infected, although such interventions could have a significant impact on population-wide HIV-1 spread. This review summarizes current knowledge of factors that influence HIV-1 infectiousness, with special attention on the role of genital tract HIV-1 as a surrogate marker of infectiousness. Epidemiologic studies have demonstrated good agreement between factors associated with increased HIV-1 transmission and increased HIV-1 genital tract shedding. Treatment of sexually transmitted diseases and initiation of antiretroviral therapy have been shown to reduce HIV-1 shedding and thus are promising interventions that may reduce HIV-1 transmission. Unresolved issues related to optimal measurement techniques for genital HIV-1, promises and limitations of antiretroviral therapy and vaccines to reduce infectiousness, and other intervention strategies still in development are reviewed.
Keywords: sexual transmission